THE REALITY OF DIVORCED WOMEN AS SINGLE PARENTS: A LEGAL REVIEW OF NAFAQAH AND CHILDREN IN PULO VILLAGE, BANTEN PROVINCE - Fitria Agustin; B. Syafuri; Nurul Ma’rifah; Naf’an Tarihoran (Universitas Serang Raya, 2025)
Single parent families are known to be mainly female. Some causes of single parent family conditions are not only due to death, but also due to the cancellation of marriage by the Court. The topic of the problem in this research is the Legal Review for the Reality of divorced women related to Nafkah and Childcare with restrictions on single parent women due to divorce. The purpose of the research is intended to find an analysis and understanding of child maintenance and care as a reality lived by women as single parents. This type of research is Juridical-Sociological / Socio Legal Research, where the problem is reviewed from the legal side, accompanied by a non-legal approach, by including social factors, and adding non-legal science studies in the research. By using Qualitative Research, data is presented in the form of descriptions and interpretations of what is found in the field. The data is presented in the form of descriptions and analyses (Analytical Descriptive), explained with statements, not numbers. Data is obtained from the location in the form of words or oral from trusted informants. Data collection was carried out with Deep Interviews, where informants tell stories, without having to answer written questions, because it is not easy to tell unpleasant experiences. The conclusion obtained is that being a Single Parent in a family is not easy, especially for a woman who has to take care of children, take care of household needs, and also become a breadwinner. According to the Marriage Law and the Compilation of Islamic Law, parenting authority is given to the mother if the child is not yet an adult, and if the mother has passed away, then parenting becomes the obligation of the father and the surviving family of the father or mother. Even if the father and mother are divorced, the father does not lose his responsibility to provide maintenance even though the child does not live with him. Keywords: Nafaqah, Parenting Authority, Single Parent